OP0011 EFFECT OF LIRAGLUTIDE ON BODY WEIGHT AND PAIN IN THE TREATMENT OF OVERWEIGHT AND KNEE OSTEOARTHRITIS: A RANDOMISED, DOUBLE-BLIND, PLACEBO-CONTROLLED STUDY. (June 2019) - Gudbergsen, Henrik; Overgaard, Anders; Henriksen, Marius; Wæhrens, Eva Ejlersen; Bliddal, Henning; Christensen, Robin; Nielsen, Sabrina Mai; Boesen, Mikael; Knop, Filip Krag; Astrup, Arne; Rasmussen, Marianne Uggen; Bartholdy, Cecilie Rødgaard; et al.
Abstract : Background: Weight loss is recommended as treatment of concomitant knee osteoarthritis (OA) and overweight. The GLP-1 receptor agonist liraglutide has been shown effective in maintaining or even further reducing weight loss, but the compound has not been tested in a population of patients with overweight and knee OA. Objectives: The objective of this trial was to investigate if liraglutide in a 3 mg/day dosage was effective in maintaining weight loss and symptomatic effects 52 weeks after an initial 8-week dietary-based weight loss intervention dosing in patients with overweight and knee OA. Methods: Patients with overweight or obesity and knee OA participated in a randomised, double blind, placebo-controlled, parallel group, single-centre trial. Patients were provided an initial 8-week run-in diet intervention (week -8 to 0) including a low-calorie diet from Cambridge Weight Plan and dietetic counselling. At week 0 patients who had lost at least 5% of their initial body weight were randomised to liraglutide 3 mg/day or placebo for 52 weeks. The co-primary outcomes were changes in body weight and the KOOS pain subscale from week 0 to 52. Trial registration: NCT02905864 . Analyses were based on the intention-to-treat population. Results: 168 patients (Kellgren-Lawrence grade 1-3) were enrolled in the initial 8-week diet intervention and 156 patients were randomised (Figure 1). Before randomisation the 156 patients had lost 12.46 kg (SD:3.82) (≈12%) and improved in KOOS pain corresponding to 11.86 points (SD:15.13) (≈19%). Baseline characteristics were similar in the intervention and control groups. From baseline to 52 weeks there was a statistically and clinically significant difference in the weight loss between the liraglutide and the placebo groups (mean -2.76 and 1.17 kg, respectively; group difference, 3.93 kg; 95%CI -6.85 to -1.02; p=0.008), there was no difference between groups in change in KOOS pain (mean changes: 0.35 and -0.55 points, respectively; group difference, 0.89 points; 95%CI -3.89 to 5.68; p=0.713). Week 52 least squares means for body weight and KOOS pain showed similar results (Figure 2). 4 patients in the intervention and 4 patients in the control groups experienced serious adverse events, and no deaths were observed. Conclusion: In overweight patients with knee OA, an 8-week low-calorie diet intervention significantly reduced body weight and knee pain. Liraglutide treatment added after the initial diet-induced weight loss provided further weight loss over 1 year but did not reduce knee pain any further compared to placebo. Disclosure of Interests: henrik gudbergsen Grant/research support from: From Novo Nordisk, Employee of: Novo Nordisk, Speakers bureau: Pfizer, Anders Overgaard: None declared, Marius Henriksen Consultant for: Advisory board member for Thuasne Group, Eva Ejlersen Wæhrens: None declared, Henning Bliddal Grant/research support from: AbbVie. Oak Foundation, Robin Christensen Grant/research support from: AbbVie Inc, and the Oak Foundation, Speakers bureau: Roche, Sabrina Mai Nielsen: None declared, Mikael Boesen Shareholder of: Image Analysis Group, UK, Grant/research support from: Image Analysis Group, Oak Foundation, EUROSTARS, Consultant for: Esaote, Eli Lilly, Celgene, Carestream, UCB, Abbvie, Pfizer, Astra Zeneca, Roche, Siemens, Image Analysis Group, Speakers bureau: Carestream, Eli Lilly, Esaote, Abbvie, UCB, Pfizer, Image Analysis Group, Filip Krag Knop Grant/research support from: AstraZeneca, Gubra, Novo Nordisk, Sanofi and Zealand Pharma, Consultant for: Amgen, AstraZeneca, Eli Lilly, Novo Nordisk, Sanofi and Zealand Pharma, Speakers bureau: Amgen, AstraZeneca, Boehringer Ingelheim, Eli Lilly, MedImmune, MSD/Merck, Mundipharma, Norgine, Novo Nordisk, Sanofi and Zealand Pharma, Arne Astrup Grant/research support from: AA is currently involved in projects conducted by research groups at Department of Nutrition, Exercise and Sport, Faculty of Science, University of Copenhagen, funded by grants from Novo Nordisk DK, & Saniona, DK, Consultant for: AA is member of scientific advisory boards for BioCare Copenhagen & Novo Nordisk DK. He acts as consultant for Acino, Switzerland & Saniona DK., Marianne Uggen Rasmussen: None declared, Cecilie Rødgaard Bartholdy: None declared, Cecilie Daugaard: None declared, Else Marie Bartels: None declared, Karen Ellegaard: None declared, Berit Lilienthal Heitmann: None declared, Lars Erik Kristensen Grant/research support from: UCB, Biogen, Janssen Pharmaceuticals, and Novartis, Consultant for: Consultant for AbbVie, Amgen, Biogen, BMS, Celgene, Eli Lilly, Janssen Pharmaceuticals, MSD, Novartis, Pfizer, Roche, Sanofi, and UCB Pharma., Speakers bureau: Pfizer, AbbVie, Amgen, UCB, BMS, Biogen, MSD, Novartis, Eli Lilly and Company, and Janssen Pharmaceuticals